Hymenochaetaceae from Paraguay: Revision of the family and new records - Maubet, Y. (2020)
A synopsis of species of Hymenochaetaceae from five departments of Paraguay (Alto Paraguay, Boqueron, Central, Cordillera and Paraguari) is presented. Thirteen species from nine genera are reported, of which eleven are recorded for the first time. Descriptions and macro-and microscopic illustrations are presented for each species. Discussions on their taxonomy and ecology are provided.